The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cancers14020301
|View full text |Cite
|
Sign up to set email alerts
|

The Decision-Making Process for Palliative Sedation for Patients with Advanced Cancer–Analysis from a Systematic Review of Prospective Studies

Abstract: Background. The involvement of patients in decision making about their healthcare plans is being emphasized. In the context of palliative sedation, it is unclear how these decisions are made and who are involved in. The aim of the study is to understand how this decision-making is taken. Method. Information from a systematic review on clinical aspects of palliative sedation prospective studies were included. PubMed, CINAHL, Cochrane, MEDLINE, and EMBASE were searched (January 2014–December 2019). Data extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The high burden imposed by palliative emergencies and poor short-term prognosis may render the patient incapable of expressing their preference. 35 Accordingly, complex collegial procedures, such as those including a third-party physician, are rare. Previous studies have emphasised that the need for timely access to palliative care teams is often unmet.…”
Section: Discussionmentioning
confidence: 99%
“…The high burden imposed by palliative emergencies and poor short-term prognosis may render the patient incapable of expressing their preference. 35 Accordingly, complex collegial procedures, such as those including a third-party physician, are rare. Previous studies have emphasised that the need for timely access to palliative care teams is often unmet.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, experts were invited at each stage of the consensus procedure to propose additional references. As additional outcomes of the PalSed project two systematic reviews of prospective studies, 2 , 17 a review on monitoring 18 and a review of European guidelines on palliative sedation 12 were published. However, due to the workflow of the PalSed project the literature identified in these reviews was only available during step 2 and 3 of the Delphi process and were then implemented in the document.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, a new terminology has been suggested, introducing the term ‘intentional sedation’, focussing on the causal role (intention to sedate) of the clinical action (sedation). 17 Even though new research on palliative sedation has been published, 2 , 17 , 18 issues such as the complexity of assessing refractory symptoms 14 , 19 or the differentiation between somatic, psychological and existential suffering 14 remain under discussion. In addition, a recent systematic review showed an underlying need to emphasise the principle of proportionality in palliative sedation practice with regard to the patient’s individual situation, considering the continuum from light to deep and from intermittent to continuous sedation.…”
Section: Introductionmentioning
confidence: 99%
“…High-quality clinical research on palliative sedation is limited [7,8,28]. Moreover, research on the decision-making process and guidelines before administering palliative sedation differ substantially across institutions, partly due to ambiguous and variable terminology [7,16,29,30]. If palliative sedation is considered and judged to be adequate and feasible by the treating physician and the multi-professional team, consultation with a palliative care specialist is strongly recommended whenever feasible.…”
Section: Guideline Recommendationsmentioning
confidence: 99%